Hierarchical flower-like nickel phenylphosphonate microspheres and their calcined derivatives for supercapacitor electrodes. Issue 16 (5th April 2017) - Zhang, Fan; Bao, Yuanyuan; Ma, Shuangshuang; Liu, Lu; Shi, Xin
Abstract : For the first time, hierarchical flower-like nickel phenylphosphonate microspheres were synthesized and applied as a high performance electrode material for pseudocapacitors. Abstract : Organic–inorganic hybrid materials applied as electrode materials for supercapacitors encounter the largest challenge of poor conductivity as a result of insulating organic groups in the frameworks. Our strategy responding to the challenge involves selection of organic groups containing a conjugated structure, and the design of hierarchical structures constituted of 1D or 2D nanometer building blocks to provide practicable conduction pathways in the frameworks. For the first time, nickel phenylphosphonate microspheres with a hierarchical flower-like structure self-assembled from layer-structured nanosheets were synthesized and successfully applied as an electrode material for supercapacitors. Encouraging pseudocapacitive performance, such as a specific capacitance of 500.8 F g −1 and remaining at 305.5 F g −1 after 1000 cycles, and a maximum energy density and power density of 17.3 W h kg −1 and 1956 W kg −1 respectively, can be achieved, which is attributed to the new electrode material's intrinsic characteristics related to the unique hierarchical flower-like structure and layer-structured nanosheets as building blocks. Furthermore, the derivatives of nickel phenylphosphonate microspheres calcined at 600 °C retain their precursor's morphology and hierarchical structure, and exhibit excellent electrochemical properties superior to that of previously reported nickel pyrophosphate. The research work presents a successful paradigm for the application of metal phosphonates as supercapacitive electrode materials and also provides a facile and feasible method for preparation of porous metal phosphate electrode materials with special morphology and hierarchical structure.